Can Horticulture be a Success Story for India? - Surabhi Mittal (Indian Council for Research on International Economic Relations (ICRIER), 2007)
India is the second largest producer of the fruits and vegetables in the world after China. Since the 1980s the international trade in fruits and vegetables has expanded rapidly. The number of commodities as well as the number of varieties produced and traded have drastically increased during the past 25 years. There is an overall increase in the demand of fruits and vegetables for consumption both in fresh and the processed form. Also there is a wide diversification in production pattern globally. Income in this sector is increasing which is driving the supply. In spite of being one of the largest producers of fruits and vegetables in the world, the export competitiveness among the Indian producers remains low. But with new marketing initiatives, the post-harvest losses and wastage due to poor infrastructure facilities such as storage and transportation are reduced to a considerable extent, yet a lot needs to be done in this sector. In an effort to overcome some of the problems associated with this sector, the case study of the successful SAFAL Market is presented in the paper. The study has observed a shift in cropping pattern in favour of horticulture in India in the past one-and-a-half decades. Analysis of the economic feasibility of this shift away from cereals to fruits and vegetable shows that it's economically viable and beneficial to shift towards horticulture production, but this diversification needs to be planned in a systematic manner. Certain strategies and policies are also suggested in this regards. The study confirms the changing consumption patterns and diversification, along with the outlook for the next 15-20 years in the light of shortage of supply to increased domestic demand. The major exports from India are mango, grapes, orange, apple, banana, mosambi, onion, potato, tomato and pumpkins. The major share of India's exports of fresh fruits and vegetables go to Bangladesh, Nepal, UAE, UK and Malaysia. Supply constraints, yield gaps and huge logistic costs affect our competitive and comparative advantage in world trade market. In this study the nominal protection coefficient and revealed comparative advantage are computed to check on the existing status. Study also identifies the potential states for the fruits and vegetables, for which India is globally competitive and has comparative advantage in production. These states should be targeted for enhancing the export potential of the country. The potential competing countries are also identified. Lessons from other developing countries focus on the growth of the horticulture sector through increased participation of small and marginal farmers in an organized manner and farmers being trained with entrepreneurial skills.
Keywords: Q13; Q17; 330; Horticulture; Cost Benefit Ratio; Competitiveness; Comparative Advantage; SAFAL Market; Gartenbau; Außenhandel; Komparativer Vorteil; Internationaler Wettbewerb; Indien